Applied Studies of Coastal and Marine Environments 2016
DOI: 10.5772/62155
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Bulk Metal Concentration and Bioavailability in Tropic Estuarine Sediments

Abstract: elements, their chemical forms and the mineral composition, organic matter (TOC) and carbonates (TIC) in surface sediments from the Cai River estuary and Nha Trang Bay were first determined along the salinity gradient. The abundance and ratio of major and trace elements in surface sediments are discussed in relation to the mineralogy, grain size, depositional conditions, reference background and SQG values. Most trace-element contents are at natural levels and are derived from the composition of rocks and soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…MPs act as vectors for pollutants due to their large specific surface area, and pose a potential threat to the environment (Koelmans et al 2016). Field studies have indicated that persistent organic pollutants (POPs) and metal pollutants adhere to the MPs (Chen et al 2018a, Koukina et al 2016, Wang et al 2017. Organic pollutants adsorbed on the MPs include dichlorodiphenyltrichloroethane, and phenylalanine 17 alpha ethinyl estradiol, etc.…”
Section: Introductionmentioning
confidence: 99%
“…MPs act as vectors for pollutants due to their large specific surface area, and pose a potential threat to the environment (Koelmans et al 2016). Field studies have indicated that persistent organic pollutants (POPs) and metal pollutants adhere to the MPs (Chen et al 2018a, Koukina et al 2016, Wang et al 2017. Organic pollutants adsorbed on the MPs include dichlorodiphenyltrichloroethane, and phenylalanine 17 alpha ethinyl estradiol, etc.…”
Section: Introductionmentioning
confidence: 99%